KCNQ1 gene variants in the risk for type 2 diabetes and impaired renal function in the Spanish Renastur cohort. (15th May 2016) - Riobello, Cristina; Gómez, Juan; Gil-Peña, Helena; Tranche, Salvador; Reguero, Julián R.; de la Hera, Jesús M.; Delgado, Elías; Calvo, David; Morís, César; Santos, Fernando; Coto-Segura, Pablo; Iglesias, Sara; et al.
Abstract: Several common KCNQ1 gene polymorphisms have been associated with the risk of type 2 diabetes (T2DM) and diabetic nephropathy. This effect is explained by the role of the kcnq1 protein as a potassium channel that in the pancreatic beta-cells drives an electrical signal that facilitates glucose-stimulated insulin secretion. The KCNQ1 gene is also expressed in the kidney, and could thus be implicated in the risk of developing impaired renal function. To test this hypothesis, we genotyped six common KCNQ1 gene variants (three single nucleotide polymorphisms, rs2237892, rs2237895, and rs231362, and three intronic indels) in 681 healthy elderly individuals (>65 years old) from the Spanish Renastur cohort. None of the six variants was associated with T2DM (180 diabetics vs. 581 non-diabetics). The intron 12 insertion allele was associated with a reduced estimated glomerular filtration rate (eGFR<60, n = 90 vs. eGFR≥60, n = 591; II vs ID + DD genotypes, p = 0.031, OR = 2.06, 95%CI = 1.12–4.14). We also performed a next generation sequencing search of variants in the coding regions of the KCNQ1 gene in 100 individuals with the extreme eGFR values. We found two rare amino acid changes (p.K393N and p.P408A) and the 393 Asn variant was found only among diabetics (n = 4; p = 0.05). The two rare alleles were present in the two eGFR groups. Our results suggest that a common KCNQ1 intron 12 indel polymorphism is a risk factor for impaired renal function independent of T2DM. If this association is confirmed by others, further research to determine the mechanism that drives this association would be warranted. Highlights: KCNQ1 gene variants were associated with diabetes and diabetic nephropathy. We determined five KCNQ1 polymorphisms in healthy elderly individuals. None of the gene variants was significantly associated with diabetes in our cohort. A common intron 12 indel was significantly associated with reduced renal filtration. KCNQ1 gene variants might be independent predictors of renal function.